Stakeholders' perceptions of continuing professional development among Nepalese nurses: A focus group study. Issue 5 (3rd January 2023) - Simkhada, Bibha; van Teijlingen, Edwin; Pandey, Apsara; Sharma, Chandra Kala; Simkhada, Padam; Singh, Devendra Raj
Abstract: Aim: This study explores perceptions of Continuing Professional Development (CPD) opportunities among stakeholders in the profession of nursing in Nepal. Design: Qualitative study using focus group discussions (FGDs). Methods: Eight FGDs were conducted in three major cities of Nepal with nursing stakeholders including nurse managers, matrons and directors/managers of private and public nursing colleges, representatives of nursing organizations, government officials, nursing academics and practitioners from the government and private sectors. The data were analysed thematically using Creswell's six steps of analysis and the Standards for Reporting Qualitative Research (SRQR) guideline was followed. Results: The study generated three major themes: (a) policy level including the national situation of CPD, political influence and training guided by the policy; (b) organizational level incorporating perceptions towards forms of CPD, staff shortage, poor staff retention, seniority for training, financial constraints and lack of continuity of training; and (c) individual level including motivation for training and lack of relevant training.